REDESIGN LIGHTING SYSTEM OF SAMSAT AND UPPD OFFICE IN SEMARANG CITY II - Syahputra Gabe Harianja; Karnoto Karnoto; Denis Denis (Universitas Diponegoro, 2019)
The study was conducted by designing a lighting system in the Central Java UPPD and SAMSAT Building, then comparing the design of the new lighting system and the design of the lighting system installed now using Dialux Evo 8.2 software, referring to SNI 03-6575-2001 for illumination values and glare levels. The results of the simulation using of lamp manufacture such is Philips found that the amount of illumination for each room that has a 350 lux lighting standard produced an illumination value of 355-410 lux. The room has a 250 lux lighting standard, resulting in a lighting level of 251-253 lux. The room that has a 200 lux lighting standard, an illumination value of 203-240 lux is produced. Spaces that have a lighting standard of 150 lux, illuminated values of 151-180 lux is produced. The room that has a 50 lux lighting standard, an illumination value of 110 lux is produced. The study was conducted in all building spaces because the lighting system before the design was not in accordance with SNI 03-6575-2001 standards.